2021
DOI: 10.3390/microorganisms9050927
|View full text |Cite
|
Sign up to set email alerts
|

Induction and Resuscitation of Viable but Nonculturable Corynebacterium diphtheriae

Abstract: Many pathogenic bacteria, including Escherichia coli and Vibrio cholerae, can become viable but nonculturable (VBNC) following exposure to specific stress conditions. Corynebacterium diphtheriae, a known human pathogen causing diphtheria, has not previously been shown to enter the VBNC state. Here, we report that C. diphtheriae can become VBNC when exposed to low temperatures. Morphological differences in culturable and VBNC C. diphtheriae were examined using scanning electron microscopy. Culturable cells pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Moreover, when VBNC cells were plated onto standard media supplemented with ROS mitigating agents like catalase or sodium pyruvate, the fraction of culturable cells increased significantly. Similar observations were made for other microorganisms (Wai et al 2000 , Masmoudi et al 2010 , Senoh et al 2015 , Hamabata et al 2021 ), showing that resuscitation of VBNC cells likely depends on their ability to neutralize highly ROS generated upon stress conditions. Notably, a recent study by Hong et al ( 2019 ) demonstrated that E. coli cells displayed a self-amplifying accumulation of toxic ROS postantibiotic treatment, which directly contributed to cell death.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, when VBNC cells were plated onto standard media supplemented with ROS mitigating agents like catalase or sodium pyruvate, the fraction of culturable cells increased significantly. Similar observations were made for other microorganisms (Wai et al 2000 , Masmoudi et al 2010 , Senoh et al 2015 , Hamabata et al 2021 ), showing that resuscitation of VBNC cells likely depends on their ability to neutralize highly ROS generated upon stress conditions. Notably, a recent study by Hong et al ( 2019 ) demonstrated that E. coli cells displayed a self-amplifying accumulation of toxic ROS postantibiotic treatment, which directly contributed to cell death.…”
Section: Discussionsupporting
confidence: 78%
“…4). We also examined catalase, a component of OADC supplementation, and its reactivation promoting effect toward VBNC Corynebacterium, Lactobacillus, Salmonella, Ralstonia and Vibrio (4752); no restorative effects were observed (data not shown). These results suggest that the effect of albumin may be due to complex functions rather than its antioxidative property.…”
Section: Discussionmentioning
confidence: 99%
“…4). We also examined catalase, a component of OADC supplementation, and its resuscitation promoting effect toward VBNC Corynebacterium, Lactobacillus, Salmonella, Ralstonia and Vibrio (Kong et al, 2004(Kong et al, , 2014Senoh et al, 2015;Liu et al, 2017;Morishige et al, 2017;Hamabata et al, 2021); no resuscitative effects were observed (data not shown).…”
Section: Bsa Promotes Resuscitation Of Vbnc M Tuberculosismentioning
confidence: 99%
“…Although the VBNC state is generally regarded as a survival strategy to against adverse conditions [4], the molecular mechanism is less reported. In previous reports, the transcriptomic approach was used to explore the mechanism of VBNC state in E. coli [18][19][20], Brettanomyces bruxellensis [21], V. alginolyticus [22], V. cholerae [23], Corynebacterium diphtheriae [24], P. syringae pv. syringae [25], Enterococcus faecalis [26], V. parahaemolyticus [27], and C. michiganensis [28].…”
Section: Introductionmentioning
confidence: 99%